2015
DOI: 10.1155/2015/363216
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hyperuricemia and Haar-Like Features on Tongue Images

Abstract: Objective. To investigate differences in tongue images of subjects with and without hyperuricemia. Materials and Methods. This population-based case-control study was performed in 2012-2013. We collected data from 46 case subjects with hyperuricemia and 46 control subjects, including results of biochemical examinations and tongue images. Symmetrical Haar-like features based on integral images were extracted from tongue images. T-tests were performed to determine the ability of extracted features to distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a previous study, Prevotella Intermedia, which is known as one of the causative bacteria of tooth decay and periodontitis, was abundant in oral microbiota of gout patients [22]. In addition, the color of the root of the tongue, which may be related to oral health and oral microbiota, is indicative of hyperuricemia [23]. Furthermore, it has been reported that abnormal findings or oral microbiota are also associated with severe asthma, cardiovascular disease, diabetes, and rheumatoid arthritis [2430].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Prevotella Intermedia, which is known as one of the causative bacteria of tooth decay and periodontitis, was abundant in oral microbiota of gout patients [22]. In addition, the color of the root of the tongue, which may be related to oral health and oral microbiota, is indicative of hyperuricemia [23]. Furthermore, it has been reported that abnormal findings or oral microbiota are also associated with severe asthma, cardiovascular disease, diabetes, and rheumatoid arthritis [2430].…”
Section: Discussionmentioning
confidence: 99%
“…In traditional Chinese medicine (TCM) theory, the exterior symptoms and signs may reflect the fundamental pathology of the internal organs. In other words, the status of the internal organs can be determined by observing exterior symptoms such as the complexion or the tongue [ 9 , 10 ]. The TCM theory of essence, qi, and spirit indicates that expression, mood, and speech reflect mental and physical health [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these two studies did not focus on diagnosing the disease or identifying the health status. Cui et al used this approach in diagnosing hyperuricemia [ 17 ]. However, only a few similar studies can be found.…”
Section: Introductionmentioning
confidence: 99%